Efficient synthesis of hydroxy-substituted cispentacin derivatives - Benedek György (EUROPEAN JOURNAL OF ORGANIC CHEMISTRY, 2008)
Starting from N-protected cis-and trans-2-aminocyclopent-3-enecarboxylic acid derivatives, isomers of 2-amino-3-hydroxycyclopentanecarboxylic acid (8 and 12) were prepared via oxazoline intermediates, whereas the stereoisomeric 2-amino-3,4-dihydroxycyclopentanecarboxylic acids 14 and 17 were synthesized by OsO4-catalyzed oxidation. The enantiomers of 8 and 14 were also prepared by the same pathway. The structures, stereochemistry and relative configurations of the synthesized compounds were proved by NMR spectroscopy. ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008).